Bible legends an introduction to Midrash - Freehof, Lillian B. (Simon) 1906-; Schwartz, Howard 1945-.; Tarlow, Phyllis (New York UAHC Press, 1987)
A collection of Jewish legends focusing on such primary characters of the book of Genesis as Adam and Eve, Noah, Abraham and Rebecca, Jacob, and Joseph.
Keywords: Legends, Jewish; Bible stories -- O.T. Genesis; Bible stories, English -- O.T. Exodus; Bible stories, English -- O.T. Genesis; Folklore; Jews -- Folklore; Midrash -- Juvenile literature; Midrash